USGA 지반에 조성된 주요 한지형 잔디의 뿌리생장과 토양물리성의 상관관계 분석 - 김경남(Kyoung-Nam Kim) (Weed & turfgrass science, 2019)
본 연구는 USGA 지반에서 주요 한지형 잔디의 표면경도 및 투수속도 차이와 이들 요인과 뿌리생장과의 상관관계를 파악해서 천연잔디구장의 설계, 시공 및 관리에 활용하고자 시작하였다. 본 실험결과 한지형 초종별 표면경도 및 투수속도에 대해 유의한 차이가 나타났다. USGA 지반에서 표면경도는 켄터키 블루그래스>퍼레니얼 라이그래스>톨 페스큐 순서로 나타났으며, 켄터키 블루그래스, 퍼레니얼 라이그래스, 톨 페스큐를 혼합 파종한 혼합구 I (KB:PR=40:60), II (KB:PR:TF=25:25:50), III (KB:PR=30:70)의 표면경도는 초종 및 혼합비율에 따라 표면경도가 가장 높았던 켄터키 블루그래스와 가장 낮은 톨 페스큐 사이로 나타났다. 투수성능이 가장 양호한 초종은 켄터키 블루그래스로 시간당 투수속도가 1,960 mm·h-1 이었으며, 반대로 가장 불량한 초종은 1,435 mm·h-1인 퍼레니얼 라이그래스로 켄터키 블루그래스에 비해 26.7% 정도 느리게 나타났다. 톨 페스큐의 시간당 투수속도는 1,890 mm·h-1로 켄터키 블루그래스와 퍼레니얼 라이그래스 사이로 나타났다. 혼합구의 투수속도는 켄터키 블루그래스 초종이 많이 혼합될수록 빨랐으며, 반대로 퍼레니얼 라이그래스의 비율이 높을수록 투수속도가 느리게 나타났다. 처리구간 표면경도 및 투수속도 차이는 초종간 생육형 및 뿌리생육 특성과 관련이 있는 것으로 판단되었으며, 잔디뿌리발달과 표면경도 및 투수속도간의 상관분석 결과 각각 r=-0.595 및 r=-0.611로 나타났다. 즉 한지형 잔디의 뿌리발달이 왕성할수록 표면경도 및 투수속도는 감소하는 경향으로 나타났다 The management of soil physical properties is one of the most basic knowledge in cultural practice for sports turfgrass design, construction, and maintenance. This study was initiated to analyze the correlation between root growth of major cool-season turfgrasses (CSG) and soil physical properties which were established on United States Golf Association (USGA) soil profile. Turfgrass entries were comprised of 3 blends and 3 mixtures from Kentucky bluegrass (KB), perennial ryegrass (PR), and tall fescue (TF). In 2-year establishment of CSG, differences were significantly observed with soil surface hardness and water infiltration rate. The highest value of soil surface hardness was associated with KB and lowest with TF. Other entries such as PR and Mixtures I (KB:PR=40:60), II (KB:PR:TF=25:25:50) and III (KB:PR=30:70) were intermediate between KB and TF, depending on turfgrass species and mixing ratio. There were also great variations in infiltration rate. KB showed the fastest speed, being 1,960 mm·h-1. But PR had the lowest rate of 1,435 mm·h-1, being 26.7% slower in water infiltration speed, as compared with KB. TF was ranked between KB and PR with a rate of 1,890 mm·h-1. As for CSG mixtures, the higher the KB, the faster the infiltration rate, while the higher the PR, the slower the rate. Differences in soil surface hardness and infiltration rate were considered to result from growth habit and root growth characteristics. The correlation analysis with rooting growth development demonstrated significant negative values on soil surface hardness (r=-0.595) and water infiltration rate (r=-0.611). These results indicated soil surface hardness and water infiltration rate were related with rooting characteristics and would be important factors to consider for the proper design, construction and management in sports turf field. KCI Citation Count: 2